(3fhQ GdfHQGS aj TQM SjQI GHf SjO GdfGSs - (3EHQGgje Hf eMeO Hf Ndjd GdnqWnQGoHodSj Ke GdMdHj, CHh GdhaGA, HQgGf GdOjf, pSrHW GHf GdnYnLej , J (B841 (3g` s; (3eMeO Hf eMeO Hf eMeO Hf CMeO, GHf nSpqjO GdfGS, GdjYeQj GdQHYj, CHh GdaJM, aJM GdOjf,J (B734 (3g` s ((3CHhGdMSf Ydj GHf MSf Hf Ydj Hf CMeO GdSQhj GdCRgQj s)
(3ChdgG (B:s
(3GdMeO ddg GdUeO, GdeJaVd HJMa GdfYe hGdahGFO, GdeMSf HGdUdGJ hGdahGFO s
(3BNQgG (B:s
(3Je GdLRA GdCh ef fhQ GdfHQGS, ai GdcdGe Ydi SjQI GHf SjO GfGS hjJdhg ai GLRA GdKGfi Gf TGA Gddg JYGdi ZRhI MeQGA GdCSO s
(3GfXQ Qbe (B859 (3JGQjNs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B269s
Keywords: (3GdJGQjNs